Masalah Tugas Perkembangan Mahasiswa dan Implikasinya Terhadap Program BK Komprehensif di Perguruan Tinggi - Emeliya Hardi; Rina Yulitri; Desri Jumiarti; Sisrazeni Sisrazeni (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
The purpose of this study was to analyze the problems experienced by IAIN Batusangkar students and their responses to BK services at IAIN Batusangkar. This research is a quantitative descriptive study, describing research findings about developmental problems experienced by students of IAIN Batusangkar. The sample was 317 people. The technique of collecting data was using the Student Developmental Task Inventory (ITP), which was analyzed by Developmental Task Analysis (ATP). From the analysis of developmental tasks, it was found that there were 20 problems experienced by students of IAIN Batusangkar which were seen from the lowest level of development of students. So the results of this developmental task can be a guide for LPBK/KM IAIN Batusangkar and for service providers in providing structured services in order to achieve ideal developmental tasks for students through comprehensive BK services including individual counseling services, group counseling/guidance, and classical services.Keywords: Task Development; Responsive service